Streets in Nablus old town: repositories for cultural identity and collective memory - Taher, Muath (2015)
"2nd International Multidisciplinary Scientific Conference on Social Sciences and Arts, SGEM2015: conference proceedings", ISBN 978-619-7105-50-6 / ISSN 2367-5659. Book 4, Vol. 1